Multi-instrument observations of ionospheric irregularities over South Africa - Amabayo, Emirant Bertillas (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2012)
The occurrence of mid-latitude spread F (SF) over South Africa has not been extensively studied since the installation of the DPS-4 digisondes at Madimbo (30.88◦E, 22.38◦S), Grahamstown (33.32◦S, 26.50◦E) and Louisvale (28.51◦S, 21.24◦E). This study is intended to quantify the probability of the occurrence of F region disturbances associated with ionospheric spread F (SF) and L-band scintillation over South Africa. This study used available ionosonde data for 8 years (2000-2008) from the three South African stations. The SF events were identified manually on ionograms and grouped for further statistical analysis into frequency SF (FSF), range SF (RSF) and mixed SF (MSF). The results show that the diurnal pattern of SF occurrence peaks strongly between 23:00 and 00:00 UT. This pattern is true for all seasons and types of SF at Madimbo and Grahamstown during 2001 and 2005, except for RSF which had peaks during autumn and spring during 2001 at Madimbo. The probability of both MSF and FSF tends to increase with decreasing sunspot number (SSN), with a peak in 2005 (a moderate solar activity period). The seasonal peaks of MSF and FSF are more frequent during winter months at both Madimbo and Grahamstown. In this study SF was evident in ∼ 0.03% and ∼ 0.06% of the available ionograms at Madimbo and Grahamstown respectively during the eight year period. The presence of ionospheric irregularities associated with SF and scintillation was investigated using data from selected Global Positioning System (GPS) receiver stations distributed across South Africa. The results, based on GPS total electron content (TEC) and ionosonde measurements, show that SF over this region can most likely be attributed to travelling ionospheric disturbances (TIDs), caused by gravity waves (GWs) and neutral wind composition changes. The GWs were mostly associated with geomagnetic storms and sub-storms that occurred during periods of high and moderate solar activity (2001-2005). SF occurrence during the low solar activity period (2006-2008)can probably be attributed to neutral wind composition changes.
Keywords: Ionosphere -- Research; Sudden ionospheric disturbances; Ionospheric storms; Solar activity; Sunspots